Bioinspired graphene-based silver nanoparticles: Fabrication, characterization and antibacterial activity. (2020) - Potbhare, Ajay K.; Umekar, Mayuri S.; Chouke, Prashant B.; Bagade, Mahendra B.; Tarik Aziz, S.K.; Abdala, Ahmed A.; Chaudhary, Ratiram G.
Abstract: Herein we present a fabrication and antibacterial assays of novel silver nanoparticles (Ag NPs) on the surface of graphene oxide (GO) nanosheets as a multifunctional antibacterial material by using Pseudomonas aeruginosa biomass extract the nanocomposites has fabricated. as a synthesized material were characterized by spectroscopic technique including XRD, FTIR, EDX, Raman and TEM. XRD analysis specified the cubic crustal structure of NCs, while TEM rendered an average particle size of 25 nm of Ag-GO NCs. As a result, the fabricated Ag-GO NCs was tested against gram-positive and gram-negative strains and the results shows the Ag-GO NCs to be more effective against gram-negative bacteria ( E.coli ).